Can you rely on Treg cells on the rebound?. Issue 12 (6th December 2014) - Teh, Charis E.; Gray, Daniel H. D.
Abstract : FoxP3 + regulatory T (Treg) cells comprise a highly dynamic population that restrains autoreactivity. Although complete or long‐term depletion of Foxp3 + CD4 + Treg cells in adult mice has been shown to result in chronic inflammation and autoimmune disease, the impact of transient Treg‐cell depletion on self‐reactive responses is poorly defined. A new study published in this issue of the European Journal of Immunology [Eur. J. Immunol . 2014. 44: 3621–3631] shows that, although transient depletion of Treg cells in mice is swiftly followed by recovery of Treg‐cell numbers, the "rebounded" population fails to maintain tolerance, culminating in severe autoimmune gastritis. This commentary explores new questions about the quantitative and qualitative aspects of Treg‐cell function in immunological tolerance raised by this study and others.